Rectal cancer: York Masan resection - Praderi, Raúl; Harretche, Martín; Terra, Eneas; Praderi, José; López, Julio; Silva, Alba (Cirugía del Uruguay, 1986)
Presenting three observations in small cancers of the rectum (anterior wall and supranal) resected through the York Mason's approach. Survival (without recidivation) from 5 to 2 years.